Abnormal Bone Morphology in Charcot-Marie-Tooth Disease. (April 2022) - Michalski, Max P.; An, Tonya W.; Haupt, Edward T.; Yeshoua, Brandon; Salo, Jari; Pfeffer, Glenn
Background: Although long suspected, it has yet to be shown whether the foot and ankle deformities of Charcot-Marie-Tooth disease (CMT) are generally associated with abnormalities in osseous shape. Computed tomography (CT) was used to quantify morphologic differences of the calcaneus, talus, and navicular in CMT compared with healthy controls. Methods: Weightbearing CT scans of 21 patients (27 feet) with CMT were compared to those of 20 healthy controls. Calcaneal measurements included radius of curvature, sagittal posterior tuberosity-posterior facet angle, and tuberosity coronal rotation. Talar measurements included axial and sagittal body-neck declination angle, and coronal talar head rotation. Surface-mesh model analysis of the hindfoot was performed comparing the average of the CMT cohort to the controls using a CT analysis software (Disior Bonelogic 2.0). Means were compared with a t test ( P < .05). Results: CMT patients had significantly less talar sagittal declination vs controls (17.8 vs 25.1 degrees; P < .05). Similarly, CMT patients had less talar head coronal rotation vs controls (30.8 vs 42.5 degrees; P < .001). The calcaneal radius of curvature in CMT patients was significantly smaller than controls (822.8 vs 2143.5 mm; P < .05). CMT sagittal posterior tuberosity–posterior facet angle was also significantly different from that of controls (60.3 vs 67.9 degrees respectively; P < .001). Surface-mesh model analysis demonstrated the largest differences in morphology at the navicular tuberosity, medial talar head, sustentaculum tali, and anterior process of the calcaneus. Conclusion: This is the first study to quantify the morphologic differences in hindfoot osteology seen in CMT patients. Patients identified with osseous changes of the calcaneus, especially a smaller axial radius of curvature, may benefit from a 3-dimensional osteotomy for correction.